Scheduling Strategy of Air-conditioning Load Response Considering User Satisfaction - Liu, Qingle; Peng, Feixiang; Li, Duanchao; Tao, Jun; Wang, Wei; Zhang, Li (IEEE Conference on Industrial Electronics and Applications (Online), 2025)
With the development of society, air-conditioning load has become an indispensable resource in demand response. Rational regulation of air-conditioning can alleviate the shortness of power resources. To address this issue, this paper proposes an air-conditioning load response scheduling strategy considering user satisfaction. Firstly, a fuzzy functional relationship between user satisfaction and air-conditioning response potential is established based on the air-conditioning aggregation model, combined with user thermal comfort. Secondly, considering the impact of electricity prices on user satisfaction, the potential of air-conditioning response is explored by formulating the electricity consumption behavior of air-conditioning users guided by the time-of-use prices Thirdly, the satisfaction of air-conditioning users involved in demand response is fully considered. The satisfaction factor is integrated into the objective function in a goal-oriented manner. Finally, a simplified distribution network system simulation analysis is carried out. The results indicate that the demand response strategy proposed in this paper can effectively exploit the potential of air-conditioning load aggregation response while ensuring user satisfaction. It also has a significant effect in promoting wind and solar energy consumption, reducing grid operation cost and decreasing the load peak-to-valley difference.